Using Clustering Technique Towards Students’ Writing Skill in Recount Text - Nurmala Hendrawaty; Nurfitria Ambarwati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2017)
Clustering is a technique to turn a broad subject into a limited and more manageable topic for short essay or text. It is a technique that can be used to generate ideas in writing. It is also known as diagramming, webbing, looping or mapping. Therefore, the research aims at finding out empirical evidence concerning whether clustering technique is effective or not for students to write a recount text. The method used in this research was quantitative, and the research design was a quasi-experiment. The sample of this research was the tenth grade students of SMK Mahadika 1 Ciracas Jakarta. The experimental class is from X AP 1, and the control class is from and X AP 3 with 30 students from each class. Based on data analysis, the range score from experimental class is 57-86, while from control class is 50-84. Furthermore, the research findings shows that tcount = 3.098 and ttable= 2,002 with the significance degree of ? = 0,05 (tcount > ttable). Sincetcount is higher than ttable, it means that H1 is accepted. It can be concluded that there is a significant effect of using clustering technique towards students’ writing skill in recount text.Keywords: Clustering Technique, Writing Skill, Recount Text